2019
DOI: 10.1242/jcs.225805
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule acetylation but not detyrosination promotes focal adhesion dynamics and astrocyte migration

Abstract: Microtubules play a crucial role in mesenchymal migration by controlling cell polarity and the turnover of cell adhesive structures on the extracellular matrix. The polarized functions of microtubules imply that microtubules are locally regulated. Here, we investigated the regulation and role of two major tubulin post-translational modifications, acetylation and detyrosination, which have been associated with stable microtubules. Using primary astrocytes in a wound healing assay, we show that these tubulin mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 50 publications
(60 reference statements)
1
53
0
Order By: Relevance
“…Furthermore, a proportion of these microtubules grow and bend to reach down towards the basal cell cortex, where they remain anchored (Etienne- Manneville et al, 2005). Also in this case, our group was able to show that microtubules run along FAs, without directly contacting them (Bance et al, 2019) (Fig. 1A,B).…”
Section: Contacting Fastouching and Grabbing Microtubules Targeting Fasmentioning
confidence: 60%
See 2 more Smart Citations
“…Furthermore, a proportion of these microtubules grow and bend to reach down towards the basal cell cortex, where they remain anchored (Etienne- Manneville et al, 2005). Also in this case, our group was able to show that microtubules run along FAs, without directly contacting them (Bance et al, 2019) (Fig. 1A,B).…”
Section: Contacting Fastouching and Grabbing Microtubules Targeting Fasmentioning
confidence: 60%
“…How microtubule stability, as characterised by microtubule detyrosination or acetylation, is controlled remains unclear. In fact, our recent observations indicate that acetylation and detyrosination are regulated independently and may have different roles that are possibly unrelated to microtubule stability (Bance et al, 2019).…”
Section: Recruitment Of Cortical Partners Near Fasmentioning
confidence: 95%
See 1 more Smart Citation
“…While HDAC6 expression and activity was proposed to promote cell migration [12,126,[136][137][138], the opposite effect was observed after the loss of αTat1 or mutation of the α-tubulin lysine 40 (K40R) [99,137,139,140]. The establishment of cell adhesion to the substrate also has implications for cell motility, and the loss of either HDAC6 or αTat1 leads to an increased focal adhesion area and number, respectively, as well as decreased dynamics [137,141]. However, other works reported that loss of αTat1 leads to a decrease in focal adhesion number [122].…”
Section: • the Cancer Tubulin Code In Cell Migration And Invasionmentioning
confidence: 99%
“…However, other works reported that loss of αTat1 leads to a decrease in focal adhesion number [122]. The basis for this discrepancy remains unclear, but it is likely associated with different experimental set ups: one study investigated the role of αTat1 in wound-induced migrating cells [137], while the other used normally growing cells were used [122], raising the possibility that αTat1 promotes focal adhesion dynamics specifically during cell migration.…”
Section: • the Cancer Tubulin Code In Cell Migration And Invasionmentioning
confidence: 99%